Overly Immersed: Understanding the Two Sides of Flow and their Implications for Mediated Work Environments - Pham, Giang V. (2020)
ABSTRACT "Flow" states- which people experience when fully focusing on an activity- are believed to be the key to peak performance and enjoyment at work. However, the positives of flow may have a potential downside- it could facilitate one activity at the cost of others by diverting people’s time and mental resources away from these tasks. The shift to remote work due to Covid-19 has given people more responsibility in terms of holding themselves accountable than what they have in the interpersonal environment. With work being fully mediated, the ability to keep up with- and switch between- tasks has become crucial, and an over engagement due to flow in one task could easily impede this ability and hinder performance. The current paper thus advocates the importance of recognizing flow as a source of both positive and negative outcomes. It aims to identify potential contextual factors that determine when flow in a mediated environment could be beneficial vs. harmful for productivity, thereby providing implications for a systematic detection and intervention of “disruptive” flow experiences in such environments. Keywords mediated work, flow, flow diversion, productivity, goal performance ABOUT THE AUTHOR/S Giang V. Pham University of Illinois at Urbana-Champaign jangphamvh@gmail.com Giang V. Pham is a doctoral student in Media and Communications at the University of Illinois at Urbana-Champaign where she received her Master’s Degree in Advertising. Her research focuses on motivated cognition and factors that impact the consumption, enjoyment, and evaluation of media and advertising. She is particularly interested in the experience of flow in mediated environments and its benefits as well as drawbacks to people's productivity and enjoyment. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).